2015
DOI: 10.1186/s12861-015-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental pulp stem cells (hDPSCs): isolation, enrichment and comparative differentiation of two sub-populations

Abstract: BackgroundHuman dental pulp represents a suitable alternative source of stem cells for the purpose of cell-based therapies in regenerative medicine, because it is relatively easy to obtain it, using low invasive procedures. This study characterized and compared two subpopulations of adult stem cells derived from human dental pulp (hDPSCs). Human DPSCs, formerly immune-selected for STRO-1 and c-Kit, were separated for negativity and positivity to CD34 expression respectively, and evaluated for cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 65 publications
6
105
1
1
Order By: Relevance
“…Interestingly, we identified 2 subpopulations of DP-MSCs in the flow cytometry analysis, which suggests the presence of multiple stem cell niches in the DP. This finding concurs with that of Pisciota et al [2015], showing that the heterogeneity of the stem cell population within human DP, particularly its peculiar embryological origin, may explain the existence of 2 different subpopulations. Of course, further studies could better sort and analyze subpopulations to identify their differences and proliferation potencies.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, we identified 2 subpopulations of DP-MSCs in the flow cytometry analysis, which suggests the presence of multiple stem cell niches in the DP. This finding concurs with that of Pisciota et al [2015], showing that the heterogeneity of the stem cell population within human DP, particularly its peculiar embryological origin, may explain the existence of 2 different subpopulations. Of course, further studies could better sort and analyze subpopulations to identify their differences and proliferation potencies.…”
Section: Discussionsupporting
confidence: 80%
“…27 This process is done to remove any cell clump, 28 and the filter pore size can be selected according to cell type. Our data showed that studies used filters with pore size of 40, 70 and 100 μm.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ISCT minimal criteria suggest that the absence of CD34 expression is a prerequisite for defining MSCs, more recent studies indicate that CD34 may be expressed in primitive pluripotent stromal stem cells but is progressively eliminated during cell culturing [63]. It has been previously shown that CD34/c-Kit and STRO-1 coexpression confirm a neural crest-derived DPSC niche [56], while, in more recent studies [61] two different (STRO-1+/c-Kit+/CD34− and STRO-1+/c-Kit+/CD34+) DPSC subpopulations with noticeable differences in their stem cell characteristics have been characterized.…”
Section: Localization and Immunophenotypic Characterization Of Denmentioning
confidence: 99%